PENGARUH PEMBELAJARAN BERBASIS MASALAH PADA KEMANDIRIAN BELAJAR MATEMATIS SISWA SMK AR-RAHMAN MEDAN - Nilam Sari (JURNAL MATHEMATIC PAEDAGOGIC, 2020)
This study aims to determine: Is the increase in learning independence of students who get problem-based learning better than students who get conventional learning. This study is a semi-experimental study with the study population as all grade X students of SMK Ar-Rahman Medan. Sample selection is done by cluster random sampling technique, samples are taken randomly and 2 classes are selected from 6 existing classes. The instrument used was a scale of learning independence. The instrument was stated to have fulfilled the content validity requirements with the reliability coefficient of the learning independence scale of 0.53. Data in this study were analyzed using nonparametric statistical analysis. Statistical analysis of the data was performed with the Mann-Whitney test analysis. The results showed that: (1) Increased learning independence of students who obtained problem-based learning was higher than students who obtained conventional learning; (2) There is a significant difference between increasing the learning independence of students who get problem based learning and students who get conventional learning;Based on the results of this study, researchers suggest that problem-based learning in vocational students can be an alternative for teachers to improve student learning independence, especially in the material system of linear equations. Keywords: Problem Based Learning Approach and Student Learning Independence